Muscular and neuromuscular control following soccer-specific exercise in male youth: Changes in injury risk mechanisms - Lehnert, M; De Ste Croix, M; Zaatar, A; Hughes, J; Varekova, R; Lastovicka, O (Scandinavian journal of medicine & science in sports, 2017)
Poor neuromuscular control has been proposed as a risk factor for non-contact injuries, thus this study aimed to explore the effects of soccer-specific fatigue on leg muscle activation, reactive strength, leg stiffness, and functional hamstring/quadriceps ratio (H/QFUNC ) in elite male youth soccer players. Outcome measures were determined in 18 youth players (age 14.4 ± 0.5 years; stature 169.4 ± 9.9 cm; mass 59.3 ± 8.9 kg; maturity offset 0.86 ± 0.88 years) pre and post simulated soccer match play (SAFT90 ). There was no fatigue-related change in the H/QFUNC ; however, reactive strength and leg stiffness were both compromised (P < 0.001) after soccer-specific fatigue. Muscle activation was also locally compromised (P < 0.001) in the medial hamstring and quadriceps but not in the lateral muscles. Where statistically significant changes were observed, the effect sizes ranged from small to large (0.33-0.97). Compromised stiffness when fatigue is present suggests an increased yielding action, greater ground contact times, greater center of mass displacement, and less efficient movement when the limb comes into contact with the ground. This combined with a reduction in medial quadriceps muscle activation may reflect poor kinetic chain control at the hip and an increase in knee injury risk.
Keywords: fotbal; Quadriceps Muscle; Soccer; cvičení; mladiství; Knee Injuries; mužské pohlaví; Athletic Injuries; reactive strength; Fatigue; Muscle Fatigue; čtyřhlavý sval stehenní; svalová únava; Humans; isokinetic; poranění kolena; leg stiffness; EMG; rizikové faktory; sportovní úrazy; Exercise; Risk Factors; Adolescent; lidé; Male